Peran Pendampingan Orangtua Sebagai Salah Satu Faktor Terkait Masalah Mental Emosional Pengguna Gadget Usia Sekolah - Hermawan, Setyo; Trisetyaningsih, Yanita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Gadget users who took advantage of the internet aged 10-14 reached 66.2%, causing emotional mental problems in children in the form of emotional disorders, social problems, and hyperactivity. In 2017, 42.7% of 75 elementary school students aged 11-12 in Semarang experienced emotional disorders due to gadget addiction. At this age the child is very easy to form, easily absorbs various information from his environment and this period really depends on the parents or caregivers.Objective: Known the relationship between the role of parental assistance and the mental emotional problems of gadget user children in SD Negeri 1 Sewon Bantul.Method: This study uses a quantitative approach correlation with cross sectional design. Sample technique, purposive sampling (41 respondents). Data collection uses a questionnaire on the role of parents and the emotional development of children of gadget users. Data analysis uses descriptive tests and correlation tests with somer's.Result: The results showed that the role of parents as a whole fell into the category of 82.9% and the emotional mental of normal children by 61.0%. The relationship between the role of parental assistance and the mental emotional problems of children using gadgets (0.033<0.05).Conclusion: There is relationship between the role of parental assistance and the mental emotional problems of children using gadgets. Parents are expected to apply the rules and understand the impact of gadget use on children.